How market orientation induces small business performance: The role of strategic fits - Quang-Huy Ngo (Gadjah Mada International Journal of Business, 2021)
The purpose of this study is to shed light on how strategic fits between market orientation and the prospector strategy leads to higher performance of small businesses in Vietnam. This study draws from the contingency theory of organization to propose that strategic fits in small businesses represent by prospector strategy's mediating effects on the link between market orientation and these small businesses' performance. Data collected from 161 small businesses in Vietnam was examined. PLS-SEM was used to assess the research framework. The results reveal that the fit between market orientation and the prospector strategy, represented by the full mediating effects of this strategy, is essential to determine the performance improvement of small businesses in Vietnam. For the findings, this study provides some practical implications for small business owners in Vietnam. This study also contributes to the strategic management literature by providing empirical evidence, which suggests the strategic fits between prospector strategy and market orientation induces performance. This study also overcomes the limitations relating to the proposals of the analytic framework to assess strategic fits. Lastly, this study extends to strategic management literature by examining the role of strategic fit in small businesses' contexts.